Comprehensive Molecular Characterizations of Chinese Patients With Different Subtypes of Lung Squamous Cell Carcinoma - Qian, Jie; Chen, Rongrong; Zhao, Ruiying; Han, Yuchen; Yu, Yongfeng (Frontiers in Oncology, 2020)
Background: This study aims to profile integrative genomic spectra of Chinese patients with different subtypes of lung squamous cell carcinoma (LUSC) and explore potential molecular prognosis factors. Methods: We retrospectively identified 204 surgically resected LUSC patients in Shanghai Chest Hospital who underwent capture-based targeted next-generation sequencing (NGS) with a panel of 68 lung cancer‐related genes from September 2017 to January 2019. NGS was used to profile comprehensive molecular characterizations. Results: Of 204 cases, 114 (55.9%) were keratinizing squamous cell carcinoma (KSCC), 77 (37.7%) were nonkeratinizing squamous cell carcinoma (NKSCC), 13 (6.4%) were basaloid squamous cell carcinoma (BSCC), respectively. All subtypes presented similarly high proportions of mutations, including TP53, CDKN2A and NOTCH1. A comparable prevalence of FGFR1 amplifications was identified between KSCC and NKSCC (11.4% versus 26.9%, p = 0.007). Compared with NKSCC, IGF1R amplifications were more frequent in BSCC (0% versus 15.4%, p = 0.019). We found cases with TP53 alterations had less EGFR alterations in KSCC (P = 0.013, OR = 0.158). Compared with TCGA cohorts, our Chinese cohorts exhibited statistic differences in both somatic mutations and signaling pathways. We found that STK 11 alterations and TOP2A alterations were significantly associated with higher risk of recurrence in patients with LUSC. Conclusions: Significant differences exist among three subtypes of LUSC in molecular characterizations.